2018
DOI: 10.1002/ccd.28038
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two different radiofrequency ablation systems for renal artery denervation: Evaluation of short‐term and long‐term follow up

Abstract: Objectives To assess the clinical efficacy of renal artery denervation (RAD) in our center and to compare the efficacy of two different radiofrequency (RF) systems. Background Several systems are available for RF renal denervation. Whether there is a difference in clinical efficacy among various systems remains unknown. Methods Renal artery denervation was performed on 43 patients with resistant hypertension using either the single electrode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…However, previous studies have shown that the EnligHTN is similar to the Simplicity radiofrequency system available clinically. 3 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have shown that the EnligHTN is similar to the Simplicity radiofrequency system available clinically. 3 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…The results indicated no change in serum creatinine after RF-RDN, no augmentation of medial damage or neointimal formation in the renal artery, and no or minimal damage to surrounding tissue. AI Raisi et al [12][13][14][15] conducted a series of experimental evaluations to investigate the efficacy of different RDN, including the Symplicity Flex system, EnligHTN system, and Symplicity Spyral system, and compared their lesion sizes to illustrate the ablation effect of different systems.…”
Section: Introductionmentioning
confidence: 99%
“…A eficácia da DSRC, portanto, pode depender do tipo de dispositivo, da modalidade de entrega de energia e, ainda, das técnicas de ablação utilizadas. Assim, questionamentos sobre qual dispositivo de radiofrequência[154][155][156] ou qual modalidade de energia empregada para ablação pode atingir maiores graus de danos aos nervos renais, que se traduzam em benefícios clínicos mais consistentes, permanecem sem respostas conclusivas e requerem estudos experimentais e clínicos adicionais. No entanto, a despeito de sua amostra pequena, o estudo incluiu um braço controlado, que constitui uma característica chave para avaliar com mais clareza o braço ativo, particularmente nesse contexto de pacientes de alto risco e prognóstico desfavorável, com taxas potencialmente elevadas de eventos adversos naturais durante o seguimento clínico.…”
unclassified